Analysis of the 3D glasses application in a spatial simulation on the basis of the architectural visualization - Smaga, Mateusz Karol; Plechawska-Wójcik, Małgorzata (Journal of Computer Sciences Institute, 2017)
The arcticle describes preparation of architectural visualization of the virtual museum. It purpose was to explore possibilities of using VR glasses, 3D scans and design aplications. During the study VR glasses showed great opportunities in the field of architectural visualisation. The results of the performance tests confirmed potencial in 3D scans and models from design applications, although they require mesh prcoessing and simplification. However, the tests showed insufficient performance of tested smartphone’s GPU, which shows that market needs to advance in this direction. This would make it possible to create better VR applications.